KOMBINASI METODE FINITE STATE MACHINE DAN GAME-BASED LEARNING PADA GAME "ESCAPE FROM COV-MADNESS" - Eka Wijaya, Daniel; Auliasari, Karina; Zulfia Zahro', Hani (JATI (Jurnal Mahasiswa Teknik Informatika), 2021)
The problem with a large number of positive cases of COVID-19 which began in early 2020 makes everyone anxious for their safety, even their own families. Lack of compliance with health protocols is one of the causes of the increasing number of positive COVID-19. Therefore, it is necessary to develop a socialization game on how to implement health protocols. Socialization using gaming media is an efficient step to make people more obedient and obedient to health protocols.In this study, researchers used a combination between the Finite State Machine (FSM) method and the Game-Based Learning method in the game. The FSM method is applied at 3 levels with different forms for each level. While the Game-Based Learning method is applied to mini-games between one of the levels in the game. This game was created using Unity3D tools as the game engine and Adobe Illustrator as the software to create character designs and the required assets.Based on the results of the tests that have been carried out, researchers used 12 data from respondents with different age ranges for each respondent in order to get good test results. The results of these tests were that 100% of respondents liked this game, 100% of respondents stated that this game provided moral values ​​in everyday life, and as many as 91.7% of respondents stated that the control in this game was running well